1997
DOI: 10.1136/fn.76.3.f168
|View full text |Cite
|
Sign up to set email alerts
|

Light reduction and the electroretinogram of preterm infants

Abstract: Aims-To examine the eVects of light on retinal development and function in preterm infants as measured by the electroretinogram (ERG). Secondary outcomes included visual acuity testing, the incidence of retinopathy of prematurity, and general wellbeing, reflected in feeding tolerance, rate of weight gain, and length of hospital stay. Methods-Eligibility criteria for enrolment were birthweight < 1250 g and gestational age < 31 weeks. Sixty one infants were randomly allocated by 6 hours after birth to a control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…Nonetheless, Boo et al (2002) found that premature neonates' exposure to cyclical twelve-hour lighting or continuous darkness did not significantly affect their weight gain (3). The results of studies by Kennedy et al (1997) and Mirmiran et al (2003) also illustrated that environmental lighting had no significant effect on neonates' weight gain (2,11).…”
Section: Such a New Environment Is Essential For The Development Of Tmentioning
confidence: 64%
See 1 more Smart Citation
“…Nonetheless, Boo et al (2002) found that premature neonates' exposure to cyclical twelve-hour lighting or continuous darkness did not significantly affect their weight gain (3). The results of studies by Kennedy et al (1997) and Mirmiran et al (2003) also illustrated that environmental lighting had no significant effect on neonates' weight gain (2,11).…”
Section: Such a New Environment Is Essential For The Development Of Tmentioning
confidence: 64%
“…A probable explanation for such contrary findings may be the differences in the gestational and the postnatal ages of the participants of these two studies. Besides, Kennedy et al (1997) used eye covers for the neonates in their target group, which might have been stressful for their participating neonates (11).…”
Section: Discussionmentioning
confidence: 99%
“…Of the studies included in the Cochrane review, three were also included in the present review (9)(10)(11). These studies (LOE 1) were RCTs in which the eyes of babies in the treatment groups were covered continuously from no more than 24 h after birth until 31 to 35 weeks' corrected gestational age, while control groups were exposed to normal NICU lighting.…”
Section: Resultsmentioning
confidence: 99%
“…All three studies used the International Classification of ROP system. Seiberth et al (9) randomly assigned 127 infants with birth weight <1501 g and gestational age at birth ≤32 weeks, and Kennedy et al (10) randomly assigned 61 infants with birth weights <1251 g and ≤31 weeks' gestational age at birth, while the Light Reduction in Retinopathy of Prematurity (LIGHT-ROP) study by Reynolds et al (11) enrolled a total of 409 infants of birth weight <1251 g and gestational age at birth <31 weeks. Each study concluded that there was no statistically significant difference in the incidence of ROP between the two groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation